2003
DOI: 10.1007/s00381-003-0770-9
|View full text |Cite
|
Sign up to set email alerts
|

Fetal brain tumors

Abstract: The tumors most frequently found were those of the choroid plexus and teratomas. Out of those 18 cases, 11 patients presented with fetal hydrocephalus, and 5 of them, who were less than 34 weeks old (gestational age), underwent repeated cephalocenteses while awaiting better conditions for delivery. Two fetuses died while in utero before any intervention had taken place and 16 underwent craniotomy after birth. Twelve of those patients are still alive, 9 of whom are considered normal. The 3 others are slightly o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0
5

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(38 citation statements)
references
References 20 publications
1
32
0
5
Order By: Relevance
“…The most frequent initial symptom reported in the literature, as in our study, is macrocephaly (in about one half of cases or more), rather than focal neurological signs, regardless of tumor histology or site [8,9,10,13,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34]. This symptom frequency is not only because the infant has open skull sutures that permit calvarial expansion in the presence of increased intracranial pressure due to hydrocephalus, a large tumor mass or both, but also due to the immaturity of the brain and the inability of the infant to complain of specific symptoms; these factors may delay diagnosis and permit tumor growth.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most frequent initial symptom reported in the literature, as in our study, is macrocephaly (in about one half of cases or more), rather than focal neurological signs, regardless of tumor histology or site [8,9,10,13,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34]. This symptom frequency is not only because the infant has open skull sutures that permit calvarial expansion in the presence of increased intracranial pressure due to hydrocephalus, a large tumor mass or both, but also due to the immaturity of the brain and the inability of the infant to complain of specific symptoms; these factors may delay diagnosis and permit tumor growth.…”
Section: Discussionmentioning
confidence: 99%
“…A location either inside or around the ventricle for these tumors accounted for the prevalence of hydrocephalus in 50–80% or more of cases [8,9,10,21,32,33] and explains the need for CSF diversion in one to two thirds of infants and neonates [10,33] as well as repeated cephalocenteses in 28% of fetuses [32]. Asai et al [22] reported that 31% of infants had intraventricular tumors with complicating hydrocephalus in the majority of cases, and that 66% of these patients required CSF diversion.…”
Section: Discussionmentioning
confidence: 99%
“…24 There have been reports of cases in which patients have survived for a long time following complete resection, 1,13,14,22 and the prognosis is considered to be greatly improved if complete resection can be achieved. 2,5 For predicting outcome, the location and size of the mass are more important than the histological grade. 10,20 Because intracranial teratomas are usually hemorrhagic tumors, a large amount of intraoperative blood loss is often inevitable during resection, sometimes reaching and even exceeding the infant's blood volume.…”
Section: Discussionmentioning
confidence: 99%
“…wrodzony czaszkogardlak znajduje się na 6 miejscu pod względem częstości występowania po potworniaku (48%), gwiaździaku (36,9%), rdzeniaku zarodkowym (16%), guzie szyszynki (6,7%) i nerwiaku zarodkowym (6%) [172]. Do objawów klinicznych guza mózgu stwierdzanego po urodzeniu należą: makrocefalia, wodogłowie, duże ciemiączka, niezrośnięte szwy czaszkowe, bradykardia, zaburzenia oddychania, sinica, senność, wymioty, drgawki [168,170,[173][174][175]. U 15% dzieci stwierdza się towarzyszące inne wady wrodzone (serca, kośćca) [168,176].…”
Section: Czaszkogardlak Wrodzonyunclassified